Co-existent extrapulmonary, extragenital tuberculosis and gynaecological tumours: a reminder to pathologists - Shamsunder, S.; Banerjee, Ananya; Mala, Y. M.; Khurana, N.; Tripathi, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Extrapulmonary and extragenital tuberculosis is rarely encountered along with gynaecological tumours or malignancy. This report presents a case series of gynaecological malignancies/tumors co-existing with extrapulmonary, extragenital tuberculosis. Pathologists should always stay open to this possibility. A high index of suspicion is needed in view of the HIV pandemic causing resurgence of tuberculosis especially in third world countries.